Vitamin D intoxication - (:unkn) unknown (TURKISH J PEDIATRICS, 2012)
Ozkan B, Hatun S, Bereket A. Vitamin D intoxication. Turk J Pediatr 2012; 54: 93-98. Vitamin D intoxication (VDI) may result from supplementation rarely, but it has been reported more frequently in recent years. This may be attributable to an increase in vitamin D supplement intake due to an understanding of the role of vitamin D (25OHD) in the pathogenesis of several diseases. The symptoms and findings associated with VDI are closely related to serum calcium concentration and duration of hypercalcemia. In patients with VDI, hypercalcemia, normal or high serum phosphorus levels, normal or low levels of alkaline phosphatase (ALP), high levels of serum 25OHD, low serum parathyroid hormone (PTH), and high urine calcium/creatinine are usually present. Serum 25OHD levels above 150 ng/ml are considered as VDI. The main goal of treatment for VDI is correction of the hypercalcemia. When the calcium concentration exceeds 14 mg/dl, emergency intervention is necessary because of the adverse effects of hypercalcemia on cardiac, central nervous system, renal, and gastrointestinal functions. However, since vitamin D is stored in fat tissues, effects of toxicity may last for months despite the removal of the exogenous source of vitamin D. Treatment for VDI includes: discontinuation of intake, a diet with low calcium and phosphorus content, intravenous hydration with saline, loop diuretics, glucocorticoids, calcitonin, and bisphosphonates. In conclusion, the diagnosis of vitamin D deficiency rickets (VDDR) without checking serum 25OHD level may cause redundant treatment that leads to VDI. All patients who are clinically suspected of VDDR should be checked for serum vitamin D status and questioned for previous vitamin D administration before starting vitamin D therapy. On the other hand, parents of all infants should be asked whether they are using dietary or oral supplements, and serial questioning may be required during supplementation to avoid excessive intake.
Keywords: vitamin D; intoxication; hypercalcemia; children; ALENDRONATE THERAPY; ORAL ALENDRONATE; D DEFICIENCY; HYPERCALCEMIA; MANAGEMENT; INFANTS